Binder for diaphragm, preparation method of binder and lithium ion battery diaphragm
By polymerizing on the surface of microsphere seeds to form a cladding layer and graft molecular chains, a high-Tg-type high-temperature resistant glue was prepared, which solved the problem that ceramic diaphragm adhesives need to be mixed with low-Tg emulsion adhesives, and achieved high bonding strength, heat resistance and low breathable value-added diaphragm adhesives.
Patent Information
- Application Number
- CN202411870749.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
AI Technical Summary
The existing high-temperature resistant adhesives for ceramic diaphragms cannot be used alone and need to be mixed with low Tg emulsion adhesives to solve the problems of diaphragm edge curl and brittle crack caused by the adhesive during the coating process.
A liquid-type high-temperature resistant glue that combines the function of ordinary emulsion diaphragm glue and high Tg solution glue is adopted. By continuing to polymerize on the surface of microsphere seeds, a coating layer and a surface graft hydrophilic molecular chain is formed, and a high Tg polymer macromolecule is further prepared in the emulsion to achieve a solution/emulsion mutual capacity system and avoid mixing with other low Tg emulsion binders.
This achieves a diaphragm adhesive that provides high bond strength and heat resistance without mixing with other low Tg emulsion adhesives, reducing the value of breathable value and improving processing performance and safety performance.
Smart Images

Figure CN119614112A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a separator binder and a preparation method thereof, and a lithium ion battery separator. Background Art
[0002] With the rapid development of the lithium-ion battery industry, the safety of lithium-ion batteries has attracted widespread attention. As the main component of lithium-ion batteries, diaphragms have an important impact on the safety, capacity, charge and discharge power, and cycle performance of lithium-ion batteries. Traditional diaphragms mainly include polyethylene diaphragms, polypropylene diaphragms, and composite diaphragms. However, due to their poor heat resistance, they shrink significantly at high temperatures, which can easily lead to short circuits between the two poles and cause safety accidents.
[0003] The emergence of ceramic diaphragms has improved the high temperature resistance of batteries to a certain extent. By coating a heat-resistant ceramic layer with a thickness of 0.5-4μm on the surface of the diaphragm, the high temperature resistance of the diaphragm has been greatly improved. High temperature resistant binder is one of the key materials of this heat-resistant ceramic layer, and the performance of the binder largely determines the performance of the ceramic diaphragm.
[0004] Currently, there are relatively few types of high-temperature resistant adhesives used for ceramic diaphragms. Although several adhesives with good heat resistance have appeared one after another, they are hard and brittle due to their high-rigidity molecular structure design. They cannot be used alone and need to be mixed with low-Tg emulsion adhesives to improve the curling and brittle cracking of the diaphragm edges caused by coating, thereby reducing the air permeability value-added of the ceramic diaphragm. Summary of the invention
[0005] In order to solve the problem in the prior art that the high temperature resistant adhesive used for ceramic diaphragms cannot be used alone and needs to be mixed with a low Tg emulsion type adhesive, the present invention provides a one-liquid high temperature resistant adhesive that has both the functions of an ordinary emulsion diaphragm adhesive and a high Tg solution adhesive, which does not need to be mixed with other low Tg emulsion type adhesives, thereby solving the problem in the prior art that the adhesive used for ceramic diaphragms needs to be mixed with a low Tg emulsion type adhesive.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A method for preparing a diaphragm adhesive comprises the following steps:
[0008] S1: mixing the coating / grafting monomer, initiator A, alkali solution and water to obtain a mixed solution;
[0009] S2: preparing microsphere seed emulsion by emulsion polymerization using seed microsphere monomers;
[0010] S3: adding a portion of the mixed solution to the seed microsphere emulsion, and terminating the reaction after keeping the mixture at 80-85° C. to obtain a reaction solution 1;
[0011] S4: adding the remaining mixed solution dropwise to the reaction solution 1, and keeping the mixture warm to obtain a reaction solution 2;
[0012] S5: cooling the reaction solution 2 to 60-70° C., adding initiator B, keeping the temperature, heating to 85-90° C., reacting, cooling to 35-45° C., adjusting the pH to 6.5-7.5, filtering, and obtaining a membrane binder;
[0013] The coating / grafting monomer is an amphiphilic or hydrophilic monomer.
[0014] Optionally, the structural formula of the coating / grafting monomer is as shown below:
[0015] R 1 -CH=CH-R 2 ;
[0016] Among them, R 1 , R 2 All selected from COOH, COONH 2 、R-OH、COONHCH 3 、COON(CH 3 ) 2 、CN、SO 3 At least one of H; R is an alkyl group.
[0017] Optionally, the coating / grafting monomer is selected from at least one of methacrylic acid, acrylic acid, acrylonitrile, itaconic acid, acrylamide, N,N-dimethylacrylamide, and N-hydroxyethylacrylamide.
[0018] Optionally, the particle size of the microsphere seeds is 0.2-1 μm.
[0019] Optionally, the glass transition temperature Tg of the microsphere seed is -20 to 50°C.
[0020] Optionally, preparing a microsphere seed emulsion by emulsion polymerization using a seed microsphere monomer includes: mixing an emulsifier with water according to a formula, adding the seed microsphere monomer, a crosslinking agent B, and an initiator C, mixing, and heating to 70-80° C. in an inert gas atmosphere for reaction to obtain the microsphere seed emulsion.
[0021] Optionally, the monomer of the seed microsphere is selected from at least one of methyl methacrylate, styrene, acrylonitrile, acrylamide, butyl acrylate, isooctyl acrylate, sodium p-styrene sulfonate, acrylic acid, isobornyl (meth)acrylate, itaconic acid, and methacrylic acid.
[0022] Optionally, the crosslinking agent is selected from at least one of glycidyl methacrylate, hydroxyethyl acrylate, hydroxyethyl acrylamide and divinylbenzene.
[0023] Another object of the present invention is to provide a separator binder, which is prepared by the above-mentioned method for preparing the separator binder.
[0024] Another object of the present invention is to provide a lithium ion battery separator, comprising the separator binder as described above.
[0025] The beneficial effects of the present invention are:
[0026] The preparation method of the adhesive for diaphragm provided by the present invention uses microsphere seeds as templates, continues polymerization on the surface thereof to form a coating layer and surface grafted hydrophilic molecular chains, and further prepares high-Tg polymer macromolecules in the emulsion to obtain a one-liquid high-temperature resistant adhesive having the functions of ordinary emulsion diaphragm adhesive and high-Tg solution adhesive, which does not need to be mixed with other low-Tg emulsion adhesives. On the basis of ensuring the bonding performance and improving the heat resistance, the air permeability value-added value is reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0028] Figure 1 Schematic diagram of the preparation process of the adhesive for the diaphragm in the present invention;
[0029] Figure 2 Schematic diagram of the composition of the adhesive for the diaphragm in the present invention;
[0030] Figure 3 Schematic diagram of glass transition temperature detection of microsphere seeds in Example 1 of the present invention;
[0031] Figure 4 is a particle size distribution diagram of the microsphere seeds in Example 1 of the present invention;
[0032] Figure 5 is a particle size distribution diagram of the binder for the diaphragm in Example 1 of the present invention;
[0033] Figure 6 is a particle size distribution diagram of the microsphere seeds in Example 2 of the present invention;
[0034] Figure 7 is a particle size distribution diagram of the binder for the diaphragm in Example 2 of the present invention;
[0035] Figure 8 is a particle size distribution diagram of the microsphere seeds in Example 3 of the present invention;
[0036] Fig. 9 This is a particle size distribution diagram of the binder for the diaphragm in Example 2 of the present invention. DETAILED DESCRIPTION
[0037] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0038] In order to solve the problem that the high temperature resistant binder for ceramic diaphragms in the prior art cannot be used alone, the present invention provides a method for preparing a binder for diaphragms, the preparation method comprising the following steps:
[0039] S1: mixing the coating / grafting monomer, initiator A, alkali solution and water to obtain a mixed solution;
[0040] wherein the coating / grafting monomer is an amphiphilic or hydrophilic monomer; preferably, the initiator A is a water-soluble initiator, and further preferably, the initiator A is selected from at least one of potassium persulfate (KPS), ammonium persulfate (APS), ammonium persulfate-Bruggolite FF6, and ammonium persulfate-sodium sulfite; preferably, the alkali solution is an aqueous sodium hydroxide solution; preferably, in this step, the amount ratio of the coating / grafting monomer, the initiator A, the alkali solution and the water is (150-160): (0.6-1): (5-6): (300-400);
[0041] In this step, corresponding additives such as PEG, CMC, PVP, PVA, etc. can be added as needed;
[0042] S2: preparing microsphere seed emulsion by emulsion polymerization using seed microsphere monomers;
[0043] S3: adding a portion of the mixed solution to the seed microsphere emulsion, preferably adding 20%-35% of the mixed solution by weight, for 15-20 minutes, and keeping it warm at 80-85°C, preferably for 1-3 hours, to terminate the reaction; wherein the method for terminating the reaction may be to terminate the reaction by adding a terminator, or by high temperature and long time reaction; continuing to keep warm for 30 minutes to obtain reaction solution 1;
[0044] Through this step, a hydrophilic short chain is grafted onto the outer shell of the microsphere seed to generate target microspheres, and a reaction solution is obtained, which is recorded as reaction solution 1; by grafting a hydrophilic short chain onto the outer shell of the microsphere seed, it is helpful to make the prepared membrane binder have both excellent dispersibility and stability; at the same time, the membrane binder has flexible bonding points, so that the membrane binder has low air permeability and good processing performance;
[0045] S4: adding the remaining mixed solution to the reaction solution 1 dropwise, preferably for 60-100 min, and keeping warm, preferably for 1 h, to obtain the reaction solution 2;
[0046] S5: Cooling the reaction solution 2 to 60-70° C., adding initiator B, preferably initiator B is a water-soluble initiator, and further preferably initiator B is selected from at least one of potassium persulfate (KPS), ammonium persulfate (APS), ammonium persulfate-Bruggolite FF6, and ammonium persulfate-sodium sulfite; keeping warm, preferably keeping warm for 0.5-1h, raising the temperature to 85-90° C., reacting, preferably keeping warm for 2h, then cooling to 35-45° C., adjusting the pH to 6.5-7.5, filtering, preferably filtering the material through a 200-mesh filter, to obtain a white emulsion, i.e., a diaphragm binder;
[0047] In this step, the emulsion prepared in step S4, i.e., reaction liquid 1, is used as a primer, and amphiphilic or hydrophilic monomers are added for copolymerization to prepare high Tg rigid macromolecular chains, thereby preparing a high-temperature resistant adhesive for diaphragm ceramics having high heat resistance, high bonding strength, low air permeability, high addition, low curling and low cracking.
[0048] The existing preparation technology of binders needs to be used together with latex glue to solve the application and processing problems such as brittle cracking and curling when the heat resistance is improved by high Tg water-based polymers. In view of the shortcomings in the current technical methods, the present invention designs a one-liquid high temperature resistant glue that has both the functions of ordinary emulsion diaphragm glue and high Tg solution glue. In the process of forming a water-soluble polymer with a high glass transition temperature, polymer microsphere seeds are introduced, and the seed microspheres are used as templates to continue polymerization on their surface to form a coating layer and surface grafted hydrophilic molecular chains. High Tg polymer macromolecules are further prepared in this emulsion, thereby realizing a solution / emulsion compatibility system, achieving point bonding and line bonding of diaphragms and ceramic particles, without the need to mix with other low Tg emulsion-type binders. The rigid polymer molecule main chain is used to resist the thermal shrinkage of the diaphragm, and the brittleness of the ceramic slurry is reduced by the point bonding of the emulsion microspheres, curling is suppressed, and processing performance is improved. At the same time, the blocking of the diaphragm gap is reduced, good air permeability is maintained, and the obstruction to lithium ion transmission is reduced.
[0049] See also Figure 1 , Figure 2As shown, the preparation path of the adhesive for the diaphragm in the present invention is as follows: first, prepare polymer seed microspheres by emulsion technology (the seed microspheres still have a large number of free radical initiation centers), add amphiphilic / hydrophilic monomers to continue copolymerization, introduce a coating layer and long-chain molecules containing hydrophilic groups on the surface of the microspheres (to impart better hydrophilicity and increase stability in aqueous solution), and wait until the active sites disappear or are greatly reduced (add a terminator to inactivate free radicals and high temperature inactivation). Further, in the above-mentioned emulsion, solution polymerization is used to prepare a water-soluble polymer macromolecule with high rigidity in the main chain, thereby preparing a solution / emulsion-compatible aqueous system adhesive with a high glass transition temperature. By adjusting the synthesis process such as monomer ratio, cross-linking monomer, addition order and reaction node, the microsphere particle size, glass transition temperature Tg, bonding peel strength, air permeability and other properties can be adjusted.
[0050] The preparation method of the adhesive for diaphragm provided by the present invention uses microsphere seeds as templates, continues polymerization on the surface thereof to form a coating layer and surface grafted hydrophilic molecular chains, and further prepares high Tg polymer macromolecules in the emulsion, thereby reducing the air permeability value-added value while ensuring the bonding performance and improving the heat resistance.
[0051] In order to prepare a high temperature resistant binder for diaphragm ceramics with high heat resistance, high bonding strength, low air permeability, high addition, low curling and low cracking, the structural formula of the preferred coating / grafting monomer of the present invention is as follows:
[0052] R 1 -CH=CH-R 2 ;
[0053] Among them, R 1 , R 2 All selected from COOH, COONH 2 、R-OH、COONHCH 3 、COON(CH 3 ) 2 、CN、SO 3 At least one of H; R is an alkyl group.
[0054] Furthermore, it is preferred that the coating / grafting monomer is at least one selected from methacrylic acid, acrylic acid, acrylonitrile, itaconic acid, acrylamide, N,N-dimethylacrylamide, and N-hydroxyethylacrylamide.
[0055] The preferred particle size of the microsphere seeds of the present invention is 0.2-1 μm, and the preferred glass transition temperature Tg of the microsphere seeds is -20 to 50°C.
[0056] Specifically, the present invention uses seed microsphere monomers to prepare microsphere seed emulsion through emulsion polymerization, including: according to the formula, after mixing the emulsifier and water, adding the seed microsphere monomers, the crosslinking agent, and the initiator C, mixing, heating to 70-80° C. in an inert gas atmosphere for reaction, preferably reacting for 30-60 minutes, to obtain the microsphere seed emulsion.
[0057] In the present invention, the mass ratio of the emulsifier, water, seed microsphere monomer, crosslinking agent and initiator C is preferably 0.3:100:(30-45):(1-2):0.5.
[0058] In order to take into account the heat resistance, processing performance and air permeability of the diaphragm binder, the present invention preferably uses a certain proportion of soft and hard monomers to generate small-particle microsphere seeds with a low glass transition temperature (Tg) through emulsion polymerization. Specifically, it is preferred that the seed microsphere monomer includes at least one monomer of the coating / grafting monomers, so that the seed microspheres have a certain hydrophilicity, which is conducive to the in situ growth of external aqueous molecular chains; and it is further preferred that the seed microsphere monomer is selected from at least one of methyl methacrylate, styrene, acrylonitrile, acrylamide, butyl acrylate, isooctyl acrylate, sodium p-styrene sulfonate, acrylic acid, isobornyl (meth)acrylate, itaconic acid, and methacrylic acid.
[0059] In the present invention, the preferred initiator C is selected from at least one of potassium persulfate, ammonium persulfate, ammonium persulfate-FF6, and ammonium persulfate-sodium sulfite; the preferred crosslinking agent is selected from at least one of glycidyl methacrylate, hydroxyethyl acrylate, hydroxyethyl acrylamide, and divinylbenzene; and the preferred emulsifier is selected from at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and sodium octyl succinate sulfonate.
[0060] Another object of the present invention is to provide a separator binder, which is prepared by the above-mentioned method for preparing the separator binder.
[0061] The adhesive for diaphragms provided by the present invention uses microsphere seeds as templates in the preparation process, continues to polymerize on the surface of the microsphere seeds to form a coating layer and surface grafted hydrophilic molecular chains, and further prepares high-Tg polymer macromolecules in the emulsion, thereby reducing the air permeability value-added value while ensuring the bonding performance and improving the heat resistance.
[0062] Another object of the present invention is to provide a lithium ion battery separator, which includes the separator binder as described above.
[0063] The lithium ion battery diaphragm provided by the present invention adopts a diaphragm binder. In the preparation process, microsphere seeds are used as templates, and polymerization is continued on the surface to form a coating layer and surface grafted hydrophilic molecular chains. High-Tg polymer macromolecules are further prepared in the emulsion. On the basis of ensuring the bonding performance and improving the heat resistance, the permeability value-added resin is reduced.
[0064] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0065] Example 1
[0066] S1: Preparation of mixed solution: 50 g acrylic acid, 10 g methacrylic acid, 20 g N, N-dimethylacrylamide, 80 g acrylamide, 0.8 g APS, 4 g PEG, 6 g 32% sodium hydroxide aqueous solution and 300 g water were mixed;
[0067] S2: Preparation of seed microsphere emulsion: 0.1 g sodium dodecylbenzene sulfonate and 100 g water were added to a reactor, and 12 g methyl methacrylate, 15 g isooctyl acrylate, 3 g acrylic acid, 2 g acrylamide, 1 g hydroxyethyl acrylamide, and 0.5 g APS were added in sequence under stirring at 200 rpm, mixed evenly, passed nitrogen, and turned on water bath heating (set temperature 80°C). At 80°C, stirred for 45 min, the reaction solution was milky white, and the microsphere seed emulsion was obtained;
[0068] S3: 115 g of mixed solution A was uniformly added to the above emulsion for 15 min, and the mixture was kept at 80°C for 1.5 h. 0.1 g of terminator FF6 was added and the mixture was kept at this temperature for 30 min to obtain reaction solution 1.
[0069] S4: Add the remaining mixed solution A dropwise into the reaction solution 1 for 90 min and keep warm for 1 h to obtain the reaction solution 2;
[0070] S5: Cool the reaction solution 2 to 65°C, and add 12g of 3% APS aqueous solution and 12g of 3% FF6 aqueous solution at the same time. Keep the temperature at 65°C for 1 hour, then raise the temperature to 90°C and continue to keep the temperature for 2 hours; cool to 40°C, adjust the pH to 7.2 with sodium hydroxide solution, filter the material with a 200-mesh filter to obtain a white emulsion, i.e., the adhesive for diaphragm.
[0071] The theoretical glass transition temperature Tg of the microsphere seeds prepared in step S2 is about 3°C according to the FOX formula. The actual glass transition temperature Tg is Figure 3 As shown, the actual glass transition temperature Tg4°C is almost consistent with the theoretical value Tg, proving that the theoretical glass transition temperature calculated by the FOX formula is more accurate.
[0072] Detect the particle size distribution of the product. The particle size distribution diagram of the microsphere seeds in step S2 is shown in Figure 4 The particle size distribution diagram of the diaphragm binder is shown in Table 1. Figure 5 Its particle size distribution is shown in Table 2.
[0073] Table 1
[0074]
[0075] Table 2
[0076]
[0077] Example 2
[0078] S1: Preparation of mixed solution: 45g acrylic acid, 5g methacrylic acid, 100g acrylamide, 1g APS, 4g PVA, 5g sodium hydroxide aqueous solution with a mass fraction of 32% and 300g water were mixed.
[0079] S2: Preparation of seed microsphere emulsion: Add 0.3g sodium succinate sulfonate and 100g water into a reactor, stir at 300rpm, add 20g butyl acrylate, 8g styrene, 3g acrylic acid, 2g hydroxyethyl acrylamide, 0.5g APS in sequence, mix evenly, pass nitrogen, turn on water bath heating (set temperature 80°C), stir at 80°C for 30min, the reaction solution becomes milky white, and the microsphere seed emulsion is obtained.
[0080] S3: uniformly add 92 g of mixed solution A to the above emulsion for 15 min, keep warm at 80°C for 1 h, add 0.1 g of terminator FF6, keep warm for 30 min, and obtain reaction solution 1;
[0081] S4: adding the remaining mixed solution A to the reaction solution 1, the dropping time is 60 min, and the temperature is kept for 1 h, to obtain the reaction solution 2;
[0082] S5: Cool the reaction solution 2 to 65°C, and add 10g of 3% APS aqueous solution and 10g of 3% FF6 aqueous solution at the same time. Keep the temperature at 65°C for 0.5h, then raise the temperature to 90°C and continue to keep the temperature for 2h; cool to 40°C, adjust the pH to 6.7 with sodium hydroxide solution, filter the material with a 200-mesh filter to obtain a white emulsion, i.e., the adhesive for diaphragm.
[0083] The theoretical glass transition temperature Tg of the microsphere seeds prepared in step S2 is calculated according to the FOX formula and is approximately -10°C.
[0084] Detect the particle size distribution of the product. The particle size distribution diagram of the microsphere seeds in step S2 is shown in Figure 6The particle size distribution diagram of the diaphragm binder is shown in Table 3. Figure 7 Its particle size distribution is shown in Table 4.
[0085] Table 3
[0086]
[0087] Table 4
[0088]
[0089] Example 3
[0090] S1: Preparation of mixed solution: 50 g acrylic acid, 10 g methacrylic acid, 90 g acrylamide, 0.6 g APS, 5 g PVA, 6 g 32% sodium hydroxide aqueous solution and 400 g water are mixed;
[0091] S2: Preparation of seed microsphere emulsion: 0.3g sodium dodecyl sulfate and 100g water were added to a reactor, stirred at 200rpm, 20g butyl acrylate, 6g methyl methacrylate, 4g styrene, 0.5g APS, 2g acrylic acid, 1g hydroxyethyl acrylamide were added in sequence and mixed evenly, nitrogen was passed through, and a water bath was turned on (the temperature was set to 75°C). At 75°C, a mixed solution of 5g acrylic acid and 8g acrylamide was added, and stirred for 60min. The reaction solution was milky white, and a microsphere seed emulsion was obtained;
[0092] S3: uniformly adding 150 g of mixed solution A to the above emulsion for 20 min, and keeping at 85° C. for 3 h to obtain reaction solution 1; since the reaction temperature in this step is relatively high and the reaction time is relatively long, no terminator is needed to terminate the reaction;
[0093] S4: adding the remaining mixed solution A to the reaction solution 1, the dropping time is 100 min, and the temperature is kept for 1 h to obtain the reaction solution 2;
[0094] S5: Cool the reaction solution 2 to 65°C, and add 10g of 5% APS aqueous solution and 10g of 5% FF6 aqueous solution at the same time. Keep the temperature at 65°C for 1h, then raise the temperature to 85°C and keep the temperature for 2h. Cool to 40°C, adjust the pH to 6.9 with ammonia solution, filter the material with a 200-mesh filter to obtain a white emulsion, i.e., the adhesive for diaphragm.
[0095] The theoretical glass transition temperature Tg of the microsphere seeds prepared in step S2 is calculated according to the FOX formula and is approximately 20°C.
[0096] Detect the particle size distribution of the product. The particle size distribution diagram of the microsphere seeds in step S2 is shown in Figure 8The particle size distribution is shown in Table 5; the particle size distribution of the diaphragm binder is shown in Fig. 9 Its particle size distribution is shown in Table 6.
[0097] Table 5
[0098]
[0099] Table 6
[0100]
[0101] The following comparative examples of the present invention are all used for comparison with Example 2.
[0102] Comparative Example 1
[0103] A typical commercially available PAA high-temperature adhesive (Derby high-temperature adhesive DS-985) is selected in combination with an emulsion adhesive (Derby DS-9260 to improve processing curling and brittle cracking).
[0104] Comparative Example 2
[0105] A typical commercially available PAA high temperature adhesive (Derby high temperature adhesive DS-985) was selected.
[0106] Comparative Example 3
[0107] S1: Preparation of mixed solution: 45g butyl acrylate, 5g methyl methacrylate, 100g styrene, 1g APS, 4g PVA, 5g 32% sodium hydroxide aqueous solution and 300g aqueous solution containing 0.9g sodium succinate octyl sulfonate.
[0108] S2: Preparation of seed microsphere emulsion: Add 0.3g sodium succinate sulfonate and 100g water into a reactor, stir at 300rpm, add 20g butyl acrylate, 8g styrene, 3g acrylic acid, 2g hydroxyethyl acrylamide, 0.5g APS in sequence, mix evenly, pass nitrogen, turn on water bath heating (set temperature 80°C), stir at 80°C for 30min, the reaction solution becomes milky white, and the microsphere seed emulsion is obtained.
[0109] S3: uniformly add 92 g of mixed solution A to the above emulsion for 15 min, keep warm at 80°C for 1 h, add 0.1 g of terminator FF6, keep warm for 30 min, and obtain reaction solution 1;
[0110] S4: adding the remaining mixed solution A to the reaction solution 1, the dropping time is 60 min, and the temperature is kept for 1 h, to obtain the reaction solution 2;
[0111] S5: Cool the reaction solution 2 to 65°C, and add 10g of 3% APS aqueous solution and 10g of 3% FF6 aqueous solution at the same time. Keep the temperature at 65°C for 0.5h, then raise the temperature to 90°C and continue to keep the temperature for 2h; cool to 40°C, adjust the pH to 6.7 with sodium hydroxide solution, filter the material with a 200-mesh filter to obtain a white emulsion, i.e., the adhesive for diaphragm.
[0112] Note: Since non-hydrophilic monomers are used, the monomers are insoluble in water and emulsifiers need to be added to disperse and mix them evenly before further reaction to prevent demulsification.
[0113] Comparative Example 4
[0114] S1: Preparation of mixed solution: 45g acrylic acid, 5g methacrylic acid, 100g acrylamide, 1g APS, 4g PVA, 5g sodium hydroxide aqueous solution with a mass fraction of 32% and 300g water were mixed.
[0115] S2: Preparation of seed microsphere emulsion: Add 0.3g sodium succinate sulfonate and 100g water into a reactor, stir at 300rpm, add 3g butyl acrylate, 23g styrene, 5g acrylic acid, 2g hydroxyethyl acrylamide, 0.5g APS in sequence, mix evenly, pass nitrogen, turn on water bath heating (set temperature 80°C), stir at 80°C for 30min, the reaction solution becomes milky white, and the microsphere seed emulsion is obtained.
[0116] S3: uniformly add 92 g of mixed solution A to the above emulsion for 15 min, keep warm at 80°C for 1 h, add 0.1 g of terminator FF6, keep warm for 30 min, and obtain reaction solution 1;
[0117] S4: adding the remaining mixed solution A to the reaction solution 1, the dropping time is 60 min, and the temperature is kept for 1 h, to obtain the reaction solution 2;
[0118] S5: Cool the reaction solution 2 to 65°C, and add 10g of 3% APS aqueous solution and 10g of 3% FF6 aqueous solution at the same time. Keep the temperature at 65°C for 0.5h, then raise the temperature to 90°C and continue to keep the temperature for 2h; cool to 40°C, adjust the pH to 6.7 with sodium hydroxide solution, filter the material with a 200-mesh filter to obtain a white emulsion, i.e., the adhesive for diaphragm.
[0119] The theoretical glass transition temperature Tg of the microsphere seeds prepared in step S2 is calculated to be about 83°C according to the FOX formula.
[0120] Binder The above-mentioned binders except for Comparative Example 1 were used to prepare high temperature resistant ceramic composite diaphragms in the following manner:
[0121] According to the weight percentage, 1.5 parts of sodium carboxymethyl cellulose (CMC) was mixed and dissolved with an appropriate amount of water, and 94 parts of boehmite powder was added and ground into a mixture slurry by a ball mill (the rotation speed of the ball tank of the double planetary ball mill was 600 rpm, the revolution speed was 300 rpm, and the ball milling was performed for 2 hours). According to the solid content, 4 parts of high-temperature binder, 0.2 parts of dispersant (BYK-346), 0.3 parts of wetting agent (104E, 67), and an appropriate amount of water prepared in the above embodiments and comparative examples were respectively stirred and uniformly adjusted to a mixed ceramic slurry with a solid content of 39%, filtered through a 200-mesh filter cloth, and the obtained mixed ceramic slurry was coated on a PP diaphragm substrate, and dried at 70°C to form a high-temperature resistant ceramic composite diaphragm with a coating thickness of 2 μm.
[0122] The binder of Comparative Example 1 was used to prepare a high temperature resistant ceramic composite diaphragm in the following manner:
[0123] According to the weight percentage, 1.5 parts of CMC were mixed and dissolved with an appropriate amount of water, and 94 parts of boehmite powder were added and ground into a mixture slurry by ball mill. 1.5 parts of a typical commercial PAA high-temperature binder (Derby high-temperature adhesive DS-985), 2.5 parts of DS-9260, 0.2 parts of a dispersant (BYK-346), 0.3 parts of a wetting agent (104E, 67) and an appropriate amount of water were added, and stirred evenly to obtain a mixed ceramic slurry with a solid content of 39%. The mixed ceramic slurry was coated on the PP diaphragm substrate and dried at 70°C to form a high-temperature resistant ceramic composite diaphragm with a coating layer thickness of 2μm.
[0124] The performance test of the prepared diaphragm is carried out as follows:
[0125] 1. Peel strength test: Referring to GB / T2790 standard, the ceramic diaphragm prepared above was cut into test strips with a width of 2 cm and a length of 10 cm, and a 180° peel strength test was performed on a tensile testing machine.
[0126] 2. Air permeability test: According to GB / T 36363-2018 standard, the diaphragm substrate before coating and the ceramic composite membrane after coating were placed in N2 at a pressure of 1.21 kPa. 2 Under the gas flow channel, record 100mL N 2 The time t passed 1 ,t 2 , calculate the ventilation value increase = 100 / (t 1 -t 2 ).
[0127] 3. Heat resistance test: Cut the obtained high temperature resistant ceramic composite film into 8cmx8cm samples, draw points at intervals of 4cm on the horizontal / vertical (M / T) central axis, and clamp them between a 200g / m 2Place the A4 paper in a 150℃ oven, take it out after 1 hour, test the distance D (denoted as Dm and Dt) between the two edge points in the M and T directions, and calculate the shrinkage rate according to the formula shrinkage rate = D*100% / 8.
[0128] The test results are shown in Table 7:
[0129] Table 7
[0130]
[0131] It can be seen from the data in the above table that, compared with the existing adhesives, the adhesives for diaphragms prepared in the embodiments of the present invention reduce the value-added permeability while ensuring the bonding performance and processing performance and improving the heat resistance.
[0132] Comparative Example 2 uses only a high temperature resistant binder (DS-985). Due to its rigid molecular structure and high Tg, the diaphragm curls severely during the coating process, the coating cracks, and the processing performance is poor. At the same time, it is easy to form a film and block pores, resulting in a high air permeability value increase, which is not conducive to the transmission of lithium ions.
[0133] The difference between Comparative Example 3 and Example 2 is that the coating / grafting monomer is replaced by a non-hydrophilic monomer. Since the non-hydrophilic monomer needs to be mixed and added to the reaction with the assistance of an emulsifier, the polymer generated according to the emulsion polymerization mechanism has a low Tg and no high-rigidity macromolecular chains. The prepared diaphragm adhesive does not have high temperature resistance, and the diaphragm melts and breaks at 150°C.
[0134] The difference between Comparative Example 4 and Example 2 is that the glass transition temperature of the microsphere seeds prepared in step S2 is 83°C. Since the Tg of the emulsion microspheres is relatively high, the toughness of the coating cannot be significantly improved. The prepared adhesive for the diaphragm has low peel strength, and the coating layer is brittle and the coating film curls severely when coating the diaphragm.
[0135] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a diaphragm adhesive, characterized in that: The steps include: S1: mixing the coating / grafting monomer, initiator A, alkali solution and water to obtain a mixed solution; S2: preparing microsphere seed emulsion by emulsion polymerization using seed microsphere monomers; S3: adding a portion of the mixed solution to the seed microsphere emulsion, and terminating the reaction after keeping the mixture at 80-85° C. to obtain a reaction solution 1; S4: adding the remaining mixed solution dropwise to the reaction solution 1, and keeping the mixture warm to obtain a reaction solution 2; S5: cooling the reaction solution 2 to 60-70° C., adding initiator B, keeping the temperature, heating to 85-90° C., reacting, cooling to 35-45° C., adjusting the pH to 6.5-7.5, filtering, and obtaining a membrane binder; The coating / grafting monomer is an amphiphilic or hydrophilic monomer.
2. The method for preparing the diaphragm binder according to claim 1, characterized in that: The structural formula of the coating / grafting monomer is shown below: R1-CH=CH-R2; Among them, R1 and R2 are both selected from at least one of COOH, COONH2, R-OH, COONHCH3, COON(CH3)2, CN, and SO3H; and R is an alkyl group.
3. The method for preparing the diaphragm adhesive according to claim 2, characterized in that: The coating / grafting monomer is selected from at least one of methacrylic acid, acrylic acid, acrylonitrile, itaconic acid, acrylamide, N,N-dimethylacrylamide, and N-hydroxyethylacrylamide.
4. The method for preparing the diaphragm binder according to claim 1, characterized in that: The particle size of the microsphere seeds is 0.2-1 μm.
5. The method for preparing the diaphragm binder according to claim 1, characterized in that: The glass transition temperature Tg of the microsphere seeds is -20 to 50°C.
6. The method for preparing the diaphragm binder according to claim 1, characterized in that: The method of preparing microsphere seed emulsion by emulsion polymerization using seed microsphere monomers includes: mixing an emulsifier with water according to the formula, adding the seed microsphere monomers, a crosslinking agent, and an initiator C, mixing, and heating to 70-80° C. in an inert gas atmosphere for reaction to obtain the microsphere seed emulsion.
7. The method for preparing the diaphragm binder according to claim 6, characterized in that: The seed microsphere monomer is selected from at least one of methyl methacrylate, styrene, acrylonitrile, acrylamide, butyl acrylate, isooctyl acrylate, sodium p-styrene sulfonate, acrylic acid, isobornyl (meth)acrylate, itaconic acid, and methacrylic acid.
8. The method for preparing the diaphragm binder according to claim 6, characterized in that: The crosslinking agent is selected from at least one of glycidyl methacrylate, hydroxyethyl acrylate, hydroxyethyl acrylamide and divinylbenzene.
9. A diaphragm adhesive, characterized in that: The method is carried out by using the method for preparing the separator binder according to any one of claims 1 to 8.
10. A lithium ion battery separator, characterized in that: The invention comprises the adhesive for diaphragm as claimed in claim 9.